Coupled multiphase thermo-hydro-mechanical analysis of supercritical CO2 injection: Benchmark for the In Salah surface uplift problem. (August 2016) - Li, Chao; Laloui, Lyesse
Highlights: A thermo-hydro-mechanical fully coupled framework for multiphase CO2 flow is proposed. Predictions are in good agreement with the field observation at KB-501 well, In Salah, Algeria. Sensibility analysis is carried out to evaluate the effects of the aquifer's Biot coefficient and the effects of the temperature. Abstract: CO2 storage in deep aquifers, which is considered one of the most viable technologies, is delivering on its promise of limiting the greenhouse effect. Nevertheless, deep aquifers may experience significant deformation and geomechanical instabilities, such as caprock failure and fault activation, when the deep aquifer is subjected to injection of a large quantity of CO2 . The overpressure that arises from this injection usually triggers the onset of these instabilities and deformations. In addition, the temperature of the injected CO2 is often lower than the in-situ temperature, which provides an additional degree of complexity to the system. These complexities are very important to properly assess the associated risks of CO2 storage in a numerical modelling framework that can be used to precisely capture the injection process. In this study, a continuum modelling approach is developed to examine the coupling of thermal, hydraulic and geomechanical processes for CO2 injection into deep aquifers. Numerical simulations are performed with a finite element reservoir model that is built upon available experimental data and real log data for the CO2 storage site at In Salah, Algeria over an injection period of four and a half years. The blind prediction by the fully coupled simulation agrees very well with the real-time monitoring of the surface uplift at In Salah. The thermo-hydro-mechanical responses are also assessed in detail, indicating that both the caprock and aquifer are subjected to high shear failure potential.